Essential work of fracture of photo-oxidized LDPE/EVA films - Fasce, Laura Alejandra (2007)
The Essential Work of Fracture approach (EWF) was used to determine how UV-C irradiation alters the fracture behaviour of LDPE/EVA films. Complementary characterization was performed by FTIR, DSC, TOM, and uniaxial tensile testing. The crosslinking reactions that govern photo-oxidation process at initial stage of exposure stiffened the amorphous phase of the polymer, leading to films with enhanced elastic modulus, yield stress and ultimate strength, but impaired strain at break. In the fracture experiments carried out on films irradiated within o and 5 days, EWF methodology requirements were met and the corresponding fracture toughness parameters (we and βwp) turned out to be sensitive to UV-C irradiation. Longer irradiation time triggered the development of microcracks, which not allowed further stable crack growth and invalidated the application of EWF approach. Copyright © 2007 WILEY-VCH Verlag GmbH & Co. KGaA.